2021
DOI: 10.1001/jamaoncol.2020.6591
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Industry Payments to Medical Oncologists in the United States Since the Inception of the Open Payments Program, 2014 to 2019

Abstract: IMPORTANCEGiven the potential for undue influence of industry-physician payments on oncology care, it is important to understand how a national transparency program may be associated with financial interactions between industry and medical oncologists. OBJECTIVE To identify trends in industry payments to medical oncologists from 2014 to 2019 and determine if the implementation of the Open Payments program is associated with changes in the frequency or value of payments or any shift in the nature of industry-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 10 publications
4
42
1
Order By: Relevance
“…Although Marshall et al reported that overall payment values and the number of physicians receiving payments declined since the introduction of the US Open Payment Database, 29 greater payments were increasingly concentrated on a smaller proportion of the US oncologists. 28 Furthermore, Kusumi et al reported that both payments and prevalence of hematologists with payments constantly increased with a significant average annual increase of 10.4% and 2.9%, respectively. As Ozaki et al previously reported, the Japanese respiratory oncologists received the highest personal payments in 2016 due to the launch of the multiple novel oncology drugs for non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…Although Marshall et al reported that overall payment values and the number of physicians receiving payments declined since the introduction of the US Open Payment Database, 29 greater payments were increasingly concentrated on a smaller proportion of the US oncologists. 28 Furthermore, Kusumi et al reported that both payments and prevalence of hematologists with payments constantly increased with a significant average annual increase of 10.4% and 2.9%, respectively. As Ozaki et al previously reported, the Japanese respiratory oncologists received the highest personal payments in 2016 due to the launch of the multiple novel oncology drugs for non-small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…(ref. [20, 29, 30, 32]) As several companies such as Shire Japan and Baxalta did not disclose the number of payment cases, the payments from these companies were excluded from the analysis of the number of cases, while the payment values were included in the analysis. To examine the concentration of payments to individual specialists, the Gini index and shares of the value of payments held by the top 1%, 5%, 10%, and 25% of specialists were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…(ref. [20, 33, 34]) As several pharmaceutical companies disaffiliated from the JPMA and newly joined the JPMA, among all 92 companies, there were 18 companies without payment data over the four years. Thus, the average and median payments for each year and the trend of payments were calculated based on payments from all 92 companies and 74 companies with payment data for the four years between 2016 and 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Further, oncologists and hematologists were increasingly targeted by the pharmaceutical companies through the several years. 4,5 This study aimed to elucidate a magnitude of pharmaceutical payments among Japanese PHOs certificated by the Japanese Society of Pediatric Hematology/Oncology (JSPHO).…”
Section: Introductionmentioning
confidence: 99%